Investigations on introducing Si and Mg into Brownmillerite - A Rietveld Refinement - Neubauer, Jürgen; Kuzel, Hans Jürgen; Sieber, Roland; Ecker, Michael (Cement and Concrete Research, 1996)
Brownmillerite (commonly C4AF) was synthesized in a laboratory furnace. The product was examined by X-ray powder diffraction and the structure was refined by the Rietveld method. Further syntheses were made under various conditions by substituting Fe2O3 by MgO + SiO2 according to the formula C4AF1-xMxSx. All samples were examined by X-ray diffraction and quantified by Rietveld method due to their content of Brownmillerite, C2S and MgO. All results show that the whole SiO2 content could be calculated as C2S. MgO could be partially found as periclase. Brownmillerite shows a shift of lattice parameters according to the solid solution series C6A2F - C2F.
UnivIS-Import:2015-03-05:Pub.1996.nat.dgeo.IGM.LM.invest